2016
DOI: 10.1017/s0025100315000183
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic correlates of lexical stress in Uyghur

Abstract: The present study examined lexical stress patterns in Uyghur, a Turkic language. The main goal of this research was to isolate and determine which acoustic parameters provide cues to stress in Uyghur. A number of studies have investigated the phonetic correlates of lexical stress across the world's languages, with stressed syllables often longer in duration, higher in pitch, and greater in amplitude. The present study systematically investigated the acoustic cues to stress in Uyghur, examining duration, fundam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…The recordings used in this paper were made in sound booths in the UCLA and University of Kansas departments of linguistics using the software Audacity. [18] shows that stress in Uyghur is reflected only by vowel length, not pitch or intensity. This suggests that although Uyghur can be described as a stress language, stress and intonation are independent.…”
Section: Data Collectionmentioning
confidence: 99%
See 3 more Smart Citations
“…The recordings used in this paper were made in sound booths in the UCLA and University of Kansas departments of linguistics using the software Audacity. [18] shows that stress in Uyghur is reflected only by vowel length, not pitch or intensity. This suggests that although Uyghur can be described as a stress language, stress and intonation are independent.…”
Section: Data Collectionmentioning
confidence: 99%
“…Previous work has claimed that Uyghur is also a stress language [18]. The author examined the acoustic correlates of stress in Uyghur and found that in both single word utterances and continuous speech, only duration served as a significant predictor of stress location.…”
Section: Past Work On Uyghurmentioning
confidence: 99%
See 2 more Smart Citations
“…Beckman & Pierrehumbert 1986;Pierrehumbert & Beckman 1988;Fujisaki & Kawai 1988;Maekawa 1999;Kubozono 2007;Venditti et al 2008;Ishihara 2011Ishihara , 2015, Korean (Hwang 2006;Lee 2007;Hwang 2011;Kim & Jun 2009), or Mandarin (Xu 1999;Gu et al 2003;Liu & Xu 2005;Chen & Gussenhoven 2008;Lee et al 2016). Besides, the existence of the consequential cross-linguistic tendencies with respect to wh-questions is not obvious either: for instance, Amharic has stress-accent (Haile 1987) but also wh-in-situ (Eilam 2008), as do Pashto (Tegey & Robson 1996;David 2014), Uyghur (Yakup & Sereno 2016;Major 2014), Marathi (Wali 2005;Rao et al 2017;Dhongde & Wali 2009), or Ancash Qechua (Hintz 2006;Cole & Hermon 1994). Actually, Basque is illuminating in this respect.…”
Section: A Radical Externalization Approach To Wh Movement Vs Wh In mentioning
confidence: 99%